Kegiatan Pemberdayaan Masyarakat di Wilayah Madewangi RW 02 Kelurahan Setiamulya Kecamatan Tamansari Kota Tasikmalaya dengan Melakukan Penyuluhan dan Pemeriksaan Kesehatan - Aliza Puziawati; Rani Aprilia; Mediana Aulia; Alpina Damayanti; Salma Faradila; Zahra Bilqis Syahidah; Andy Muharry (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Hypertension is one of the main health problems faced by people around the world, including Indonesia. Hypertension is known as a "silent killer" because it often does not show symptoms until it reaches a serious stage. At the Tamansari Health Center in Tasikmalaya City, hypertension is the highest disease most suffered by the community with a total of 586 cases from January to October 2024. The high prevalence of hypertension in the Tamansari Health Center work area, a prevention and control program is needed through screening or early detection programs and counseling about hypertension. The implementation method carried out in this community service is to provide information using the lecture or counseling method. To measure public knowledge, pre-test and post-test are carried out. In addition to providing counseling, this activity also provides basic health checks. Based on the results obtained, there was a difference in the level of community knowledge before and after the provision of counseling which can be seen from the difference in the average percentage of pre-test and post-test.